The Risk of Nosocomial Transmission of Rift Valley Fever. - Nasser A Al-Hamdan; Anil A Panackal; Tami H Al Bassam; Abdullah Alrabea; Mohammed Al Hazmi; Yagoub Al Mazroa; Mohammed Al Jefri; Ali S Khan; Thomas G Ksiazek (PLoS Neglected Tropical Diseases)
In 2000, we investigated the Rift Valley fever (RVF) outbreak on the Arabian Peninsula-the first outside Africa-and the risk of nosocomial transmission. In a cross-sectional design, during the peak of the epidemic at its epicenter, we found four (0.6%) of 703 healthcare workers (HCWs) IgM seropositive but all with only community-associated exposures. Standard precautions are sufficient for HCWs exposed to known RVF patients, in contrast to other viral hemorrhagic fevers (VHF) such as Ebola virus disease (EVD) in which the route of transmission differs. Suspected VHF in which the etiology is uncertain should be initially managed with the most cautious infection control measures.